Omega-3 fatty acids supplementation and oxidative stress parameters: A systematic review and meta-analysis of clinical trials - Heshmati, Javad; Morvaridzadeh, Mojgan; Maroufizadeh, Saman; Akbari, Abolfazl; Yavari, Mahsa; Amirinejad, Ali; Maleki-Hajiagha, Arezoo; Sepidarkish, Mahdi (Pharmacological research, 2019)
[Display omitted] Omega-3 fatty acids (omega-3 FAs) supplementation effects on oxidants and antioxidants are always controversial. Oxidative stress (OS) is one of the major mechanisms that contribute to the pathogenesis of several chronic diseases. The present systematic review and meta-analysis aimed to summarize the finding of randomized clinical trials (RCTs) examining the effects of omega-3 FAs on OS markers. Five databases including PubMed, Embase, Scopus, Web of science, and Cochrane were searched up to May 5th, 2019 with no language restriction. RCTs included if they compared OS indices among subjects who received omega-3 FAs supplements and subjects who supplemented with placebo. To estimate the effects of omega-3 FAs supplementation, standardized mean difference (SMD) with 95% confidence intervals (95% CI) were pooled using random effects model. Of 5,887 publications, 39 trials involving 2,875 participants were included for the meta-analysis. The pooled analysis of data indicated that omega-3 FAs significantly increased serum total antioxidant capacity (TAC) (SMD: 0.48, 95% CI: 0.23, 0.72, P< 0.001; I2= 60%), glutathione peroxidase (GPx) (SMD: 0.73, 95% CI: 0.30, 1.16, P= 0.001; I2= 83%) activity and decreased malondialdehyde (MDA) (SMD= −0.42, 95% CI: −0.62, −0.21; P < 0.001; I2= 74%) compared to the placebo group. However, the effects of omega-3 FAs on nitric oxide (NO) (SMD: −0.17 , 95% CI: −0.77, 0.43, P = 0.57; I2= 91%), reduced glutathione (GSH) (SMD= 0.23, 95% CI= −0.17, 0.64, P= 0.25; I2= 75%), superoxide dismutase (SOD) (0.12 , 95% CI: −0.40, 0.65, P= 0.64; I2= 89%) and catalase (CAT) (0.16, 95% CI: −0.33, 0.65, P= 0.52; I2= 75%,) activities was not significant. Supplementation with omega-3 FAs significantly improves MDA, TAC levels, and GPx activity. Thus, omega-3 FAs can be mentioned as enhancer factors in antioxidant defense against reactive oxygen species (ROS).